Critical review on porous material manufacturing techniques, properties & their applications. (2021) - Goyal, Bhupesh; Pandey, Akash
Highlights: Space holder is one of the advanced and successful methodology for the manufacturing of metal foam. Arrangement of sand balls in different orientation provides better strentgth and efficiency for the thermal applications. Reduced cost of space holder technique makes it convenient for most of the researchers. Abstract: Generally, porosity is not a desirable characteristic of any material. In today's Industrial scenario, this parameter becomes necessity of materials for different applications like structural, solar absorbers, and sound absorption as well as biomedical applications. Metal foams are cellular structures contain porosity which increases mechanical, thermal and other physical properties of conventional materials. There are manufacturing issues concern with these materials like homogeneity and location of pores, controlling of parameters. In this article, the techniques of manufacturing of porous materials are discussed with their limiting parameters and pros & cons. Powder metallurgy is found suitable for better porosity but the cost for this process constrain its usage among the researchers and Industry as well. Space holder method is one of the found appropriate among all other used for the manufacturing of open and closed cell foam in perspective of cost as well porosity. The orientation of space holder plays a crucial role for the development of better porous object. This article reviews the different methods of manufacturing and their properties for the better future perspective in terms of cost, structure and application of porous foams.